The role of halal attribute as halal product positioning in determining consumer purchase intention - Siti Nurhazirah Abu Ashari; Che Aniza Che Wel; Siti Ngayesah Ab Hamid (Universiti Kebangsaan Malaysia, 2022)
This conceptual paper aims to investigate halal product attributes as halal product positioning in determining consumer purchase intention. This paper will review previous literature from marketing and social science perspectives. To focus on the halal market segment, this study seeks to address the issue of positioning dimensions that are in line with shariah requirements. The elements of halal product attribute discovered in this study range from safety, purity, product ingredient, and halal logo. In the context of this study, it is predicted that consumers, Muslims, and non-Muslims will behave predictably while purchasing halal food products, as proposed by Ajzen 1991. The Theory of Planned Behaviour will be used as an underpinning theory that clarifies how individual human thoughts or perceptions are shaped or impacted by a person's desire to engage in a particular behaviour. However, this study does not provide any empirical findings which mark the limit of the research.